Manajemen Risiko dalam Pengeboran Eksplorasi Panas Bumi di Indonesia - Daniel W Adityatama; Dorman P Purba; Farhan Muhammad (Swara Patra, 2019)
Drilling is one of the critical components that significantly impact geothermal project development cost. In general, there are two major risks associated with drilling, consisting of resource risks and other risks. Resource risks are mainly associated with temperature and permeability. A robust conceptual model built from reliable data is necessary to assess both of resource risks and assist the well targeting process. Other risk comprises of drilling infrastructure, drilling operation issues, environmental aspect, and local community issue. The variation of drilling objectives in each stage of the project (exploration, appraisal, development) requires different strategies in order to minimize the associated risk and project cost. This preliminary study aims to summarize the thinking process or main considerations when developing the exploration drilling strategy which accommodate subsurface, environmental, drilling and construction perspectives based on literature reviews and authors experience. The result of this study is expected to provide a generic guideline on decision making process during developing geothermal exploration drilling strategy in Indonesia.